READING HABITS IN DIGITAL ERA: A RESEARCH ON THE STUDENTS IN BORNEO UNIVERSITY - Tanjung, Firima Zona; Ridwan, Ridwan; Gultom, Uli Agustina (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
This research aims to explore the current reading habits of university students. Moreover, it aims to determine the effects of widespread use of the internet and other digital resources in reading habits and to give some possible recommendation to improve studentsâ reading habits in the digital era. The research design was descriptive survey research. The instrument of the research was questionnaire, which is based on Akarsu and Dariyemez (2014) and Chauhan and Lal (2012). The participants of the research were 320 students studying in six majors in Faculty of Teachers Training and Education at Borneo University. They were selected through the cluster random sampling. The questionnaire involved six categories, namely demographic information, frequency of items read, contents of online reading, online activities, content first clicked when online, and techniques to develop reading habits. All research data was analyzed using SPSS Statistics 22 program.Â DOI: doi.org/10.24071/llt.2017.200209